Analisis Pengaruh Citra Merek, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk (Studi Kasus Pembelian Produk Capa Oil) - Maritha, Rilo Fajar; Ningsih, Pertiwi Ratna; Anindyastri, Ranty; Apriani, Delfi Dwi; Mangifera, Liana (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
In Indonesia, the agricultural sector is one of the business activities involving many stakeholders. One of the agricultural commodity products that have a high enough potential is papaya fruit. Almost all parts of the papaya plant can be utilized, ranging from fruit, leaves, to stems. But besides that, so far papaya seeds are not used properly, so it only ends up being waste. According to research conducted by Wardani in Ahmad and Adriyanto (2019), it is mentioned that papaya seeds contain flavonoids, alkaloids, tannins, saponins, and steroids that are efficacious to eradicate mosquitoes. From this, we make products in the form of essential oils made from papaya seeds with the trademark Capa Oil. This research is intended to find out the influence of brand image, price, and product quality on capa oil purchasing decisions in the Greater Solo region. The results of this study show that the brand image, price, and quality of products influence the purchase decision of Capa Oil in the Greater Solo region.